THE CONTENT OF USING EDUCATIONAL DICTIONARIES IN MOTHER LANGUAGE AND READING LESSONS (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the content of using educational dictionaries in native language and reading lessons in primary education. The role of educational dictionaries in developing pupils’ vocabulary, reading comprehension, spelling literacy, pronunciation skills and independent learning activity is revealed. The methodological possibilities of using explanatory, spelling, orthoepic and picture dictionaries in the process of native language and reading lessons are discussed. It is substantiated that systematic work with educational dictionaries helps primary school pupils consciously understand word meanings, enrich their speech, analyze texts and express their thoughts correctly and fluently.